Future vehicles: the effect of seat configuration on posture and quality of conversation. - Fiorillo, Iolanda; Piro, Silvana; Anjani, Shabila; Smulders, Maxim; Song, Yu; Naddeo, Alessandro; Vink, Peter (Ergonomics, 2019)
The percentage of passengers that prefer travelling in groups is increasing. In most vehicles, passengers sit side by side and need to turn their body to be engaged in the conversation with their fellow travellers. However, rotating the body could lead to discomfort which influences conversation quality. The aim of this research is to study the effect of seat configuration on the (dis)comfort experience, conversation quality and posture. Experiments in which participants were asked to talk to each other while sitting at the same distance (1 m) were conducted in four seating arrangements (with seat-belts on), where the angle between the forward directions of two seats were positioned at 0° (side by side), 22.5°, 90° and 120° (almost opposite each other), respectively. Optical tracking has been deployed and the collected data were processed with MatLab® to acquire postural angles over time. Questionnaires were also used to evaluate the perceived (dis)comfort and the quality of the conversation. Experiment results indicate that the 120° configuration scored the best in the overall comfort and the quality of conversation, but only slightly better than the 90° configuration. Practitioner summary: Seating side by side is not optimal to have a comfortable conversation with your seatmate. To improve comfort and quality of conversation in future vehicles, we tested four seating arrangements analysing the effect of seat layout on (dis)comfort experience. Statistical analysis of objective and subjective data shows the optimal configuration for a comfortable conversation. Abbreviation: LPD: localized postural discomfort; PDF: probability density function; OCRA: occupational repetitive action